Identifying the Semantic Orientation of Foreign Words - Awadallah, Ahmed; Abu-Jbara, Amjad; Jha, Rahul; Radev, Dragomir (Proceedings of the 49th Annual Meeting of the Association for Computational Linguistics:shortpapers, 2011)
We present a method for identifying the positive or negative semantic orientation of foreign words. Identifying the semantic orientation of words has numerous applications in the areas of text classification, analysis of product review, analysis of responses to surveys, and mining online discussions. Identifying the semantic orientation of English words has been extensively studied in literature. Most of this work assumes the existence of resources (e.g. Wordnet, seeds, etc) that do not exist in foreign languages. In this work, we describe a method based on constructing a multilingual network connecting English and foreign words. We use this network to identify the semantic orientation of foreign words based on connection between words in the same language as well as multilingual connections. The method is experimentally tested using a manually labeled set of positive and negative words and has shown very promising results.